THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN LANGUAGE ACQUISITION. (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: This article explores the transformative impact of artificial intelligence (AI) on methodologies for language learning and instruction. It identifies a range of AI tools, including intelligent tutoring systems, natural language processing applications, and adaptive learning platforms, which customize educational experiences to meet the unique needs of individual learners. The benefits of these technologies encompass enhanced learner engagement, personalized feedback, and the capacity to analyze performance data to inform instructional strategies. Moreover, the article investigates how AI augments traditional pedagogical approaches, facilitating a more interactive and immersive educational environment. By incorporating AI into language education, educators can employ innovative strategies that accommodate diverse learning styles and enhance overall language proficiency. The efficacy of these AI-enhanced methodologies is assessed through case studies and empirical research, revealing significant improvements in learner outcomes. Ultimately, the article advocates for the widespread integration of AI in language education to harness its full potential and address the challenges encountered by both learners and educators